Supplementary Health Insurance from the consumer point of view: Are Israelis consumers doing an informed rational choice when purchasing Supplementary Health Insurance?. Issue 6 (June 2017) - Kaplan, Giora; Shahar, Yael; Tal, Orna
Highlights: The majority of Israelis voluntarily purchased supplemental health insurance. The public shows low level of knowledge about the insurance. Three different measurements were used to evaluate knowledge. Knowledge is a basic condition to an intelligent use of insurance's benefits. Abstract: Background: The National Health Insurance Law in Israel ensures basic health basket eligibility for all its citizens. A supplemental health insurance plan (SHIP) is offered for an additional fee. Over the years, the percentage of supplemental insurance's holders has risen considerably, ranking among the highest in OECD countries. The assumption that consumers implement an informed rational choice based on relevant information is doubtful. Are consumers sufficiently well informed to make market processes work well? Objectives: To examine perspectives, preferences and knowledge of Israelis in relation to SHIP. Methodology: A telephone survey was conducted with a representative sample of the Israeli adult population. 703 interviews were completed. The response rate was 50.3%. Findings: 85% of the sample reported possessing SHIP. This survey found that most of the Israeli public parched additional insurance coverage however did not show a significant knowledge about the benefits provided by the supplementary insurance, at least in the three measurements used in this study. Conclusions, policy implications and recommendations: The scope of SHIP acquisition is very broad and cannot be explained in economic terms alone. Acquiring SHIP became a default option rather than an active decision. It is time to review the goals, achievements and side effects of SHIP and to create new policy for the future.